2022
DOI: 10.1001/jamanetworkopen.2022.23325
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Net Benefits of Adult Deceased Donor Kidney Transplantation for a Patient on the Preemptive Waiting List vs a Patient Receiving Dialysis

Abstract: IMPORTANCE Preemptive kidney transplantation is the preferred treatment for end-stage kidney disease. However, deceased donor (DD) kidneys are limited, and the net benefit of allocating kidneys to a preemptively waitlisted patient rather than to a patient receiving dialysis is unclear.OBJECTIVE To estimate the net benefit and costs of allocating kidneys to preemptively waitlisted patients vs those receiving dialysis. DESIGN, SETTING, AND PARTICIPANTSThis medical decision analytical model used data from the 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…A recent economic evaluation suggested that preemptive transplantation may lower the overall societal benefit of deceased organ transplantation; however, that analysis did not consider the discard of high-KDPI kidneys. 29 The recent National Academies of Sciences and Engineering and Medicine consensus study report highlighted the socioeconomic disparities in access to preemptive transplantation and suggested removing preemptive wait time as a factor in organ allocation to improve equity in transplant. 30 However, a fundamental factor contributing to disparities in organ access to transplantation is the insufficient organ supply, and therefore, policy changes to improve equity that might limit organ utilization may not be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…A recent economic evaluation suggested that preemptive transplantation may lower the overall societal benefit of deceased organ transplantation; however, that analysis did not consider the discard of high-KDPI kidneys. 29 The recent National Academies of Sciences and Engineering and Medicine consensus study report highlighted the socioeconomic disparities in access to preemptive transplantation and suggested removing preemptive wait time as a factor in organ allocation to improve equity in transplant. 30 However, a fundamental factor contributing to disparities in organ access to transplantation is the insufficient organ supply, and therefore, policy changes to improve equity that might limit organ utilization may not be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation earlier in the kidney disease process has prognostic advantages compared to any exposure to dialysis. 8 The benefit of early transplantation is commensurate with a recent survey of 605 patients waiting for a kidney transplant, focused on trade-off preferences between kidney quality and waiting time. In that study, a majority (61%) of respondents explicitly preferred shorter waiting times even at the expense of kidney quality.…”
Section: Proposal: An End-to-end Tivbc Modelmentioning
confidence: 95%
“…Kidney transplantation represents the optimal choice for selected patients with endstage renal disease. Compared to dialysis, transplantation improves patient survival and quality of life and reduces cardiovascular morbidity [1][2][3][4]. For kidney transplantation, the healthcare costs are significantly lower than long-term dialysis expenses [5][6][7].…”
Section: Introductionmentioning
confidence: 99%